Formation of Phenotypic Characteristics of Imported "Holstein" Breed Cows with Similar Genotype In Adaptation to Climate (Texas Journal of Agriculture and Biological Sciences, 2023)
The method of selection of good genotypes from similarity genotypes of imported Holstein cattle typical of German and Slovenian breeding is accelerated in breeding. Selection-genetic indicators of cattle were studied according to breeding certificates of cattle. Genotype-environment interaction revealed the genetic potential of breeding and productivity of improving breeds.